Android application for monitoring solid waste & public cleansing inventory data at Arau perlis / Muhamad Firdaus Ibrahim - Ibrahim, Muhamad Firdaus (2019)
The inventory map of solid waste and public cleansing are very important for E-Idaman Company to calculate the amount of claim of their service to the Perbadanan Sisa Pepejal. E-Idaman Company needs to printed map to identify the location of solid waste for verification and to show the inventory data of an area in many times that cause increasing the company costing and it not a handy equipment. This paper presents a study of using Android application to help E-Idaman Company have better platform to display the inventory map of solid waste and public cleansing in Arau, Perlis. The system use geographical information system (GIS) for processing the data of solid waste inventory and display the inventory in Android Application. The development of system is using Android Studio and ArcGIS 10.4.1. The result demonstrated that Android Application is a flexible tool with reasonable speed for developing solid waste management application and the inventory will display. The result feedback from user testing show that the majority of the user are positively agreed with the efficiently of this application in monitoring inventory data. User can easily find the location of solid waste by using this application. The map will display and give the information that need to be verifying after data editing before claim money to Perbadanan Pengurusan Sisa Pepejal dan Pembersihan Awam. PPSPPA. This application can help E-Idaman Company has a better platform and increasing the efficient in monitoring progress work include data collection.